Egypt - Wilson, Susan L. (Milwaukee, Wisconsin Gareth Stevens Publishing, 1999)
An overview of Egypt, including an in-depth section on a variety of topics that make the country unique.
includes bibliographical references and index
10 years and up
Keywords: Egypt -- Juvenile literature